The Implementation of Contextual Language Learning Through Field Trip Activities in Arabic Vocabulary Learning - Thoyibah, Naim Hikmatut; Habibah, Nur Faiz; Buana, Ba'iq Kurnia (Study Program of Arabic Language Teaching, 2026)
This study aims to analyze the implementation of Contextual Language Learning through field trip activities in Arabic vocabulary (mufradat) learning at MTs Silahul Muslimin Banyuwangi, East Java. The research was conducted at the Tegaldlimo Village Hall area, which provides a contextual environment including gazebos, open fields, highways, rice fields, and a stadium. The method used is descriptive qualitative research with data collection techniques including observation, interviews, and documentation. The research subjects consisted of 18 students, teachers, and the principal. Data analysis employs the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results of the study indicate that before the intervention, students experienced boredom, low motivation, and passivity in memorizing mufradat. However, implementing a field trip with the theme